Co-cultivo fúngico como estratégia para obtenção de metabólitos biologicamente ativos - Silva, Airton Damasceno (2021)
In this work, the bactericidal, antiprotozoal, and inhibition of cathepsin V proteolytic activity of extracts from the axenic cultivation of six fungal species (Fusarium guttiforme, Pestalotiopsis diospyri, Phoma caricae-papayae, Colletotrichum horii, Phytophthora palmivora, and C. gloeosporioides) and all combinations of co-cultures among them were evaluated, resulting in 57 co-cultivation extracts. The results obtained showed that the co-culture increased the biological activity of the samples since all the extracts active against super resistant bacteria, Trypanosoma cruzi, and Leishmania infantum were obtained from co-culture combinations. Bacterial growth was inhibited totally or partially by 46% of the extracts. Two of them that contained mostly fusaric and 9,10-dehydrofusaric acids were exceptionally active. The presence of the fungus F. guttiforme in co-cultures may be associated with the high biological activity of these extracts against L. infantum. A single axenic culture considerably decreased the proteolytic activity of cathepsin V, being an exception to an observed trend. Thus, the results of biological activities indicated that the fungal co-cultivation increased the biological potential of the samples. Principal Component Analysis (PCA) of the 1H NMR spectra of the 63 extracts allowed the development of a new method to assess fungicidal activity and antagonism between fungal species within a collection. The results showed that the developed method was able to predict fungicidal activity and antagonism between species. Traditional in vitro antifungal tests of active and inactive extracts were performed in order to prove the predictions made by the PCAs. The results obtained showed that the developed method is an excellent tool to obtain and evaluate, simultaneously, bioactive samples because it was able to predict the fungicidal activity of 5 different extracts in a collection of 63 samples against 4 fungi of different genera, which would be more difficult, laborious and time consuming if they were rehearsed at random, allowing time and money savings. Finally, in order to investigate environmentally friendly alternatives in the control of diseases caused by anthracnose and black rot, this work evaluated the chemical profile of volatile organic compounds produced by the fungus F. guttiforme in the presence of the fungi C. horii, C. gloeosporioides, and P. caricae-papayae. The volatiles produced by F. guttiforme significantly inhibited the mycelial growth of phytopathogens C. horii (91.7%), C. gloeosporioides (93.7%), and P. caricae-papayae (92.5%). The production of the kaur-15-eno and kaur-16-en diterpenes by F. guttiforme may be associated with a possible long-distance defense mechanism as well as with the observed fungistatic activity. The inhibition results indicate, even in a preliminary way, that these diterpenes are promising biocontrol agents against the phytopathogens P. caricae-papayae, C. horii, and C. gloeosporioides.